Metodologias ativas no ensino de enfermagem perioperatória: estudo bibliométrico - COELHO, Andreza da Silva (2020)
The present study aims to evaluate the incidence of the use of active methodologies in perioperative nursing education in national scientific publications, from 1989 to 2019. A descriptive research was performed, for which the technique of Quantitative approach bibliometrics, through search in specialized databases BVS - BIREME in the following indexers: LILACS; MEDLIDE and BDENF. Using the filters: full text available, MEDLINE database, LILACS, BDENF - Nursing (Brazil); Portuguese language; Main subject: Perioperative nursing and teaching. For sample selection, the following inclusion criteria were adopted: articles published in Portuguese and; complete articles; whose title portrayed the theme defined in the descriptors. Time frame for the study in question was 30 years. The sample of this study consisted of 04 publications, which were selected after reading and thorough analysis. The 04 articles selected for this study included practices that cover fundamental aspects of the meaningful teaching proposal through the development of action mechanisms in the formative environment of professionals and students. However, it was not possible to identify classroom or service use through the delimitation of technique described in the various publications that portray active teaching methodologies. This scenario proved to be fundamental to conduct research focused on which methodologies are most effective, as well as to survey which institutions are already applying this new method of teaching and learning and what were the long / short term benefits within of the area of operation of the health professional .